Self-esteem, major satisfaction, appearance satisfaction, A Study on the Relationship of Employment Stress - Lee, Hwa-Myung; Park, Hyo-Jin; Yoo, Eun-Ju (韓國컴퓨터情報學會論文誌, 2021)
This study aims to identify the relationship among self-esteem, major satisfaction, appearance satisfaction, and employment stress of college students and to suggest suggestions for this. The subjects of this study were students in B metropolitan city, and data analysis was conducted using SPSS WIN/22.0 program. The result of the study showed that the difference in employment stress according to general characteristics was significant in grade (f=4.25, P=0.01), religion (t=0.70), department and department (F=7.50, P=.0001), personality (F=6.406, P=0.001), university life satisfaction (f=8.09, P=0.001), and average score (f=5.37, P=0.005). The employment stress of the subjects was negatively correlated with self-esteem(r=-.439, p<.001), major satisfaction(r=-.377, p<.001), and appearance satisfaction(r=-.273, p<.001).Based on the results of the study, it is necessary to develop an integrated program to improve self-esteem, major satisfaction, and appearance satisfaction in order to reduce the employment stress of college students, and repetitive studies are required to explore various factors. 본 연구는 대학생의 자아존중감, 전공만족도, 외모만족도, 취업스트레스의 관계를 확인하고, 이에 대한 제언을 제시하고자 한다. 연구의 대상은 B광역시에 소재한 재학생을 대상으로 실시하였으며, 자료분석은 SPSS WIN/22.0 프로그램을 활용하여 분석 하였다. 연구결과 일반적인 특성에 따른 취업스트레스의 차이는 학년(F=4.25, P=0.01), 종교(t=0.70), 학과 및 계열(F=7.50, P=.0001), 성격(F=6.406, P=0.001), 대학 생활만족도(F=8.09, P=0.001), 평균 성적(F=5.37, P=0.005) 에서는 유의하게 나타났다. 대상자의 취업 스트레스는 자아존중감(r=-.439, p<.001), 전공만족도(r=-.377, p<.001), 외모만족도(r=-.273, p<.001)에서 부적 상관관계 있었다. 연구결과를 바탕으로 대학생의 취업 스트레스를 감소시키기 위해서는 자아존중감, 전공만족도, 외모만족도을 높이기 위한 관련된 통합적 프로그램을 개발하는 것이 필요하고, 다양한 변인에 대한 반복적 연구가 요구된다.